Genetics of Alzheimer’s Disease and Frontotemporal Dementia - Nacmias, B.; Piaceri, I.; Bagnoli, S.; Tedde, A.; Piacentini, S.; Sorbi, S. (Current Molecular Medicine, 2014)
The genetics of neurodegenerative diseases has an important role to clarify the pathogenetic mechanism, the diagnosis and finally the therapeutic and ethical implications. Moreover, the genetic approach to the study of the main clinical forms of dementia (Alzheimer’s disease-AD and Frontotemporal Dementia-FTD) suggests clinical guidelines for helping families to navigate through these complexities. AD and FTD are multifactorial, genetically complex diseases involving many candidate genes. Mutations in three genes (i.e. Amyloid Precursor Protein, APP; presenilin 1, PSEN1; presenilin 2, PSEN2) have been linked to 50% of all familial forms of AD (FAD). Genome wide association studies (GWAS) have involved an increasing number of genes with a possible role in the disease pathogenesis. Up to now, the genetics of familial forms of FTD is related to 7 genes: the microtubule-associated protein tau (MAPT) progranulin (GRN), the valosin-containing protein (VCP), chromatin-modifying 2B (CHMP2B), the TARDNA binding protein 43 encoding gene (TARBDP), fused in sarcoma (FUS) and the last hexanucleotide expansion repeats in the open reading frame of chromosome 9 (C9orf72). Pre-test counseling and the identification of genetic defects are important in both patients and asymptomatic at risk family members.
Keywords: mutation